2018
DOI: 10.1016/j.ijscr.2018.10.078
|View full text |Cite
|
Sign up to set email alerts
|

A surgical case of aortic stenosis with recurrent gastrointestinal bleeding: Heyde syndrome

Abstract: HighlightsWe report successful surgical treatment of Heyde syndrome.The incidence of Heyde syndrome is expected to increase in aging population.Heyde syndrome should be considered in AS patients with gastrointestinal bleeding.Radical surgery should be performed regardless of gastrointestinal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…However, in patients with severe aortic stenosis, GI bleeding in the absence of angiodysplasias has been reported. These patients are referred to as 'GI bleeding not related to angiodysplasias' [6]. Our case was similar without identifiable angiodysplasias on endoscopy.…”
Section: Discussionsupporting
confidence: 50%
“…However, in patients with severe aortic stenosis, GI bleeding in the absence of angiodysplasias has been reported. These patients are referred to as 'GI bleeding not related to angiodysplasias' [6]. Our case was similar without identifiable angiodysplasias on endoscopy.…”
Section: Discussionsupporting
confidence: 50%
“…Various other studies have shown similar laboratory deviations in patients with aortic valve stenosis (12,27), dysfunctional aortic or mitral valve replacement, severe aortic or mitral valve regurgitation (28,29) and in patients with acquired von Willebrand syndrome type 2A (30). It was also reported that the altered laboratory parameters normalized after the repair of an aortic valve stenosis (30)(31)(32).…”
Section: Discussionmentioning
confidence: 69%
“…It reduces the mechanical shear stress on the HMW vWF multimers inhibiting their cleavage by ADAMTS13 and consequently improves coagulation abnormalities implicated in Heyde's syndrome. There are several observational studies that have demonstrated potential therapeutic benefits of AVR [45][46][47][48][49][50][51][52][53]. All studies were published between 2010 and 2020; cessation of gastrointestinal bleeding following AVR was the most measured outcome.…”
Section: Aortic Valve Replacementmentioning
confidence: 99%